Analysis of Pedagogical Practices Carried Out in Continuing Education Activities for Physics Teachers: Limits and Possibilities - Gatti, Sandra Regina Teodoro [UNESP]; Nardi, Roberto [UNESP] (Springer Nature, 2018)
The chapter deals with a general methodological and epistemological contribution to continuing education activities for physics teachers. Researchers on science teaching seem to point to a consensus on the importance of the historical and philosophical approach to teaching. Nevertheless, the pedagogical practice developed in classroom hardly ever embodies such recommendations. In this research, the authors planned a continuing education course and followed the development of five in-service physics teachers during the school year of 2008. The researchers discussed with teachers, focusing on their experiences, and seeking to assist them in the construction of alternatives means of observing and understanding the students’ work. The authors seek to revisit the training actions by discussing the propositions and perceptions of two of the participants and the respective impacts of the experience, 3 years later, when one of them became a supervisor to pre-service teacher.